Pendampingan Moderasi Beragama di Pesantren Mahasiswa Institut Ummul Quro Al-Islami Bogor Berbasis Podcast di Media Sosial - Hilman Fauzi Patahilah; Abdul Rauf (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2025)
The rise of radicalism and intolerance, particularly among young people with limited access to credible religious information in digital media, poses a serious challenge to national harmony. Religious education in Islamic boarding schools (pesantren) plays a strategic role in preventing the spread of extremism. This community service activity was conducted at Institut Ummul Quro Al-Islami (IUQI) Bogor through the YouTube platform during the second and third weeks of July 2025 at the IUQI campus podcast studio. The method employed was Participatory Action Research (PAR), involving students actively in the design and production of dialogical podcast content. The results show that podcasts are an effective medium for promoting moderate, inclusive, and contextual understandings of Islam. Students were trained to think critically, reject fanaticism, and serve as agents of peace in society. Publishing the content through YouTube effectively reached a wider and younger audience in a modern way. Therefore, this program not only benefited the students but also expanded the dissemination of religious moderation values within the broader community.